Painful knee joint after ACL reconstruction using biodegradable interference screws- SPECT/CT a valuable diagnostic tool? A case report - Hirschmann Michael T; Adler Tom; Rasch Helmut; Hügli Rolf W; Friederich Niklaus F; Arnold Markus P (BMC, 2010)
Abstract With the presented case we strive to introduce combined single photon emission computerized tomography and conventional computer tomography (SPECT/CT) as new diagnostic imaging modality and illustrate the possible clinical value in patients after ACL reconstruction. We report the case of a painful knee due to a foreign body reaction and delayed degradation of the biodegradable interference screws after ACL reconstruction. The MRI showed an intact ACL graft, a possible tibial cyclops lesion and a patella infera. There was no increased fluid collection within the bone tunnels. The 99mTc-HDP-SPECT/CT clearly identified a highly increased tracer uptake around and within the tibial and femoral tunnels and the patellofemoral joint. On 3D-CT out of the SPECT/CT data the femoral graft attachment was shallow (50% along the Blumensaat's line) and high in the notch. At revision arthroscopy a diffuse hypertrophy of the synovium, scarring of the Hoffa fat pad and a cyclops lesion of the former ACL graft was found. The interference screws were partially degraded and under palpation and pressure a grey fluid-like substance drained into the joint. The interference screws and the ACL graft were removed and an arthrolysis performed. In the case presented it was most likely a combination of improper graft placement, delayed degradation of the interference screws and unknown biological factors. The too shallow and high ACL graft placement might have led to roof impingement, chronic intraarticular inflammation and hence the delayed degradation of the screws. SPECT/CT has facilitated the establishment of diagnosis, process of decision making and further treatment in patients with knee pain after ACL reconstruction. From the combination of structural (tunnel position in 3D-CT) and metabolic information (tracer uptake in SPECT/CT) the patient's cause of the pain was established.